Employment transitions with high unemployment and a small informal sector: Examining worker flows during normal and recessionary periods in South Africa - Shakeba Foster (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper examines employment transitions in the South African labour market. Using the Post-Apartheid Labour Market Series, it analyses flows between the formal sector, informal sector, and unemployment, paying specific attention to how these flows differ during recessions. It explicitly considers heterogeneity within the informal sector by separately accounting for wage employment and self-employment as well as upper-tier and lower-tier informal sector segments. Transition probabilities are estimated using dynamic discrete choice models, and the extent to which transitions affect changes in real wages is estimated using a linear model. The results provide evidence of heterogeneity within the informal sector and segmentation between wage employment and self-employment. They also show a lag in the employment impacts following a recession. Finally, the paper provides suggestive evidence that the upper-tier segment of the informal sector acts as a buffer during recessionary periods by absorbing labour that would otherwise be unemployed or relegated to precarious lower-tier informal employment.
Keywords: J46; J62; O12; O17; 330; informal employment; employment transitions; recession; South Africa